Understanding the development of tuberculous granulomas: insights into host protection and pathogenesis, a review in humans and animals - Lyu, Jiwon; Narum, Drew E.; Baldwin, Susan L.; Larsen, Sasha E.; Bai, Xiyuan; Griffith, David E.; Dartois, Véronique; Naidoo, Threnesan; Steyn, Adrie J. C.; Coler, Rhea N.; Chan, Edward D. (Frontiers in Immunology, 2024)
Granulomas, organized aggregates of immune cells which form in response to Mycobacterium tuberculosis (Mtb), are characteristic but not exclusive of tuberculosis (TB). Despite existing investigations on TB granulomas, the determinants that differentiate host-protective granulomas from granulomas that contribute to TB pathogenesis are often disputed. Thus, the goal of this narrative review is to help clarify the existing literature on such determinants. We adopt the a priori view that TB granulomas are host-protective organelles and discuss the molecular and cellular determinants that induce protective granulomas and those that promote their failure. While reports about protective TB granulomas and their failure may initially seem contradictory, it is increasingly recognized that either deficiencies or excesses of the molecular and cellular components in TB granuloma formation may be detrimental to the host. More specifically, insufficient or excessive expression/representation of the following components have been reported to skew granulomas toward the less protective phenotype: (i) epithelioid macrophages; (ii) type 1 adaptive immune response; (iii) type 2 adaptive immune response; (iv) tumor necrosis factor; (v) interleukin-12; (vi) interleukin-17; (vii) matrix metalloproteinases; (viii) hypoxia in the TB granulomas; (ix) hypoxia inducible factor-1 alpha; (x) aerobic glycolysis; (xi) indoleamine 2,3-dioxygenase activity; (xii) heme oxygenase-1 activity; (xiii) immune checkpoint; (xiv) leukotriene A4 hydrolase activity; (xv) nuclear-factor-kappa B; and (xvi) transforming growth factor-beta. Rather, more precise and timely coordinated immune responses appear essential for eradication or containment of Mtb infection. Since there are several animal models of infection with Mtb, other species within the Mtb complex, and the surrogate Mycobacterium marinum – whether natural (cattle, elephants) or experimental (zebrafish, mouse, guinea pig, rabbit, mini pig, goat, non-human primate) infections – we also compared the TB granulomatous response and other pathologic lung lesions in various animals infected with one of these mycobacteria with that of human pulmonary TB. Identifying components that dictate the formation of host-protective granulomas and the circumstances that result in their failure can enhance our understanding of the macrocosm of human TB and facilitate the development of novel remedies – whether they be direct therapeutics or indirect interventions – to efficiently eliminate Mtb infection and prevent its pathologic sequelae.